JAK/STAT pathway: Extracellular signals, diseases, immunity, and therapeutic regimens - Hu, Qian; Bian, Qihui; Rong, Dingchao; Wang, Leiyun; Song, Jianan; Huang, Hsuan-Shun; Zeng, Jun; Mei, Jie; Wang, Peng-Yuan (Frontiers in Bioengineering and Biotechnology, 2023)
Janus kinase/signal transduction and transcription activation (JAK/STAT) pathways were originally thought to be intracellular signaling pathways that mediate cytokine signals in mammals. Existing studies show that the JAK/STAT pathway regulates the downstream signaling of numerous membrane proteins such as such as G-protein-associated receptors, integrins and so on. Mounting evidence shows that the JAK/STAT pathways play an important role in human disease pathology and pharmacological mechanism. The JAK/STAT pathways are related to aspects of all aspects of the immune system function, such as fighting infection, maintaining immune tolerance, strengthening barrier function, and cancer prevention, which are all important factors involved in immune response. In addition, the JAK/STAT pathways play an important role in extracellular mechanistic signaling and might be an important mediator of mechanistic signals that influence disease progression, immune environment. Therefore, it is important to understand the mechanism of the JAK/STAT pathways, which provides ideas for us to design more drugs targeting diseases based on the JAK/STAT pathway. In this review, we discuss the role of the JAK/STAT pathway in mechanistic signaling，disease progression, immune environment, and therapeutic targets.